CONCEPTUAL MODEL OF ELECTRONIC CONTENT COMMERCE SYSTEMS - Vysotska, V.; Chyrun, L. (Radio Electronics, Computer Science, Control, 2014)
The given article is devoted to the development of standardized methods and software of Web content processing in e-business systems. The model of electronic content commerce systems is developed. The article is devoted to the development of unified methods and software tools for processing information resources in the electronic content commerce systems. A new detailed classification of electronic commerce systems and electronic content commerce systems is proposed. A formal model and generalized typical architecture of electronic content commerce systems are declared. Architecture and models of electronic content commerce systems are built. A new approach to application and implementation of business processes is formulated for the construction of systems of electronic content commerce. A complex method of content forming, the operational method of content management and complex method of content support are developed. Software tools of content formation, management and support are developed. Methods of designing and implementation of electronic content commerce systems on the example of online newspapers, which reflects the results of theoretical research, are developed.